Horizontal Heat Flux Spread in an Inner Corner of Buildings - Daniela Šejnová Pitelková; Petr Hejtmánek; Vladimír Mózer (Safety)
This study investigates fire separation distances as essential means of passive fire protection in building design. The focus is on the inner corner configuration of building exterior walls, which represents the worst-case scenario for façade fire spread outside of a building. The inner-corner configuration appears to increase the intensity of the radiative heat flux due to reflection and reradiation of heat. Comprehensive approaches for determining fire separation distances around the various façade geometries can be found, but none of them is focused on detailed descriptions of the unprotected area in an inner corner. A medium-scale scenario was chosen and was experimentally validated with a radiant panel for a better understanding of heat flux spread. This paper compares the experiment with analytical and numerical models. The analytical model is based on the Stefan–Boltzmann law and the calculated configuration factor as per Eurocode 1. The numerical model combines radiative and convective components of the heat flux because convection is non-negligible near the heat source. Experimental data confirm the prediction based on the numerical and analytical model and show agreement. The final increase in heat flux due to the corner configuration investigated at the medium scale reaches up to 29%.